Pretreatment neutrophil-to-lymphocyte ratio predicts the prognosis in patients with metastatic prostate cancer. Issue 1 (December 2016) - Kawahara, Takashi; Yokomizo, Yumiko; Ito, Yusuke; Ito, Hiroki; Ishiguro, Hitoshi; Teranishi, Jun-ichi; Makiyama, Kazuhide; Miyoshi, Yasuhide; Miyamoto, Hiroshi; Yao, Masahiro; Uemura, Hiroji
Abstract Background The neutrophil-to-lymphocyte ratio (NLR), a simple marker of the systemic inflammatory response in critical care patients, has been suggested as an independent prognostic factor for several solid malignancies. We investigated the utility of pretreatment NLR as a prognosticator in patients who presented with metastatic prostate cancer. Methods We first investigated the correlation between NLR and prostate-specific antigen (PSA) levels in 1464 men who had both tests and were found to have prostate cancer on their biopsies at our institution from 1999 to 2015. We then assessed the relationship between pretreatment NLR and the prognosis in 48 patients who were diagnosed with prostate cancer metastasized to the lymph node and/or bone. Results The NLR value was significantly elevated in men with higher PSA than in those with lower PSA (p < 0.001). In patients with metastatic prostate cancer, NLR (cut-off point of 3.37 determined by the AUROC curve) was correlated with both cancer-specific (p = 0.018) and overall (p = 0.008) survivals. Conclusions Pretreatment NLR may function as a new biomarker that precisely predicts the prognosis in patients with metastatic prostate cancer.